The Implementation of E-speak in EFL Classroom: What do teachers think? - Oktalia, Dwi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The development of technology rapidly affects the education field. Internet connection may ease teachers and learners in getting the learning source including audio for listening activity which can be downloaded easily. Even though it is easy to get listening materials, there is no guarantee that every listening material will cover studentsâ needs or learning objective. The possible solution to this problem is creating the listening material by using Text to Speech. Text to speech namely E-speak may convert text into an audio. It can help teachers to solve the lack of listening material issue. Furthermore, it is also important to know the quality of the output from the E-speak and it can be known from the teachersâ perception. Therefore, the researcher is interested in investigating EFL teachersâ perceptions toward the use of E-speak in creating listening materials. This study used qualitative method with individual interview technique. There were eight EFL teachers who served as the sample of this research. Several steps were done in order to gain teachersâ perceptions toward the use of E-Speak: (1) computer training was done to make EFL teachers familiar with the E-speak; (2) the listening material produced by teachers was put in Google site to be delivered to students; (3) an interview was done to gain EFL teachersâ perceptions toward E-Speak. The findings show that EFL teachers give positive responses toward the integration of E-speak. EFL teachers found it useful to use this digital approach in the language learning process.